2019
DOI: 10.3390/f10090785
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up Sap Flow Measurements from the Stem Scale to the Individual Scale for Multibranched Caragana Korshinskii on the Chinese Loess Plateau

Abstract: The traditional heat balance method for measuring plant sap flow (SF) becomes troublesome and uneconomic for multibranched shrub species if all their stems are used for the measurement. The objectives of this study were to explore specific relationships between stem-scale SF and plant morphological traits and then to scale up SF measurements from the stem scale to the individual scale for Caragana korshinskii Kom., a dominant shrub species on the Chinese Loess Plateau. Sap flow was measured for twenty-one stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…The average soil bulk density is 1.2 g cm −3 in the 0–180 cm soil layer. Rain‐fed farmlands, native shrub–grasslands, sparse forestlands, and fallow croplands are the main land use types in the watershed (Wang, Shen, et al, 2019). Moreover, the natural vegetation in the study area included sparse grasses, such as Stipa bungeana and Heteropappus altaicus .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average soil bulk density is 1.2 g cm −3 in the 0–180 cm soil layer. Rain‐fed farmlands, native shrub–grasslands, sparse forestlands, and fallow croplands are the main land use types in the watershed (Wang, Shen, et al, 2019). Moreover, the natural vegetation in the study area included sparse grasses, such as Stipa bungeana and Heteropappus altaicus .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study in this area identified a satisfactory method to upscale SF from measured stem scales to individual scales for C. korshinskii (Wang, Shen, et al, 2019). The individual‐scale total canopy transpiration (T, kg shrub −1 ) and water use efficiency (WUE, kg m −3 shrub −1 ) of C. korshinskii were calculated during the growing seasons from the stem‐scale SF data (Tsuruta et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant transpiration is conducted via stomatal processes and the hysteresis between environmental factors and the SSF can be regarded as the adaptation of plants to environmental factors caused by water limitation (Matheny et al, 2014;Ma et al, 2017;Zha et al, 2017;Hong et al, 2019;Wang et al, 2019). Our results show that the daily cycle for PAR, Ta, and VPD (24 h) lags behind that for the SSF (Figure 6), which is in agreement with previous studies (Ma et al, 2017;Hong et al, 2019;Wang et al, 2019). Generally, the maximum PAR occurs at noon, while the maximum temperature and the maximum VPD usually appear in the afternoon.…”
Section: Influence Of Environmental Factors On the Stem Sap Flowmentioning
confidence: 99%
“…In general, per‐tree transpiration often scales with tree size. Variations among trees are thus often explained by biometric variables, among which stem diameter is often applied (Dierick & Hölscher, 2009; Kotowska et al, 2021; Meinzer et al, 2001; Vertessy et al, 1995; Wang et al, 2019; Yue et al, 2008). However, crown dimension‐related metrics such as crown projection area were reported to perform better than stem diameter for predicting transpiration, for example, across 32 study sites in lowland Sumatra (Röll et al, 2019).…”
Section: Introductionmentioning
confidence: 99%